Evaluation of organochlorine compounds in peregrine falcon (Falco peregrinus) and their main prey (Columba livia) inhabiting central Spain - Merino, Rubén; Bordajandi, Luisa R.; Abad Holgado, Esteban; Rivera Aranda, Josep; Jiménez, Begoña (Environmental Toxicology and Chemistry, 2005)
6 pages, 3 figures, 1 table.-- PMID: 16152983 [PubMed]. The population of peregrine falcon (Falco peregrinus sbs. brookei) inhabiting the Regional Park of southeastern Madrid (RPSM), Spain, has experienced an increase of unsuccessful pairs (from 15% among a total of 20 pairs in 1995 to 55% among a total of 18 pairs in 2001). Traditionally, this area has been known to be contaminated with organochlorine compounds and toxic metals, which are known to be deleterious to the reproductive system of birds. During the breeding seasons of 2000 and 2001, contaminant residues were measured in unhatched eggs of peregrine falcons and liver of their main prey, to determine if they could be affecting the survival of the population. The most abundant contaminants were ortho–polychlorinated biphenyls (ortho-PCBs), ranging from 202.56 to 3,335.16 ng/g (wet wt) in falcon eggs and from 10.25 to 53.51 ng/g (wet wt) in pigeon livers. In all samples, the 2,3,7,8-substituted polychlorinated dibenzo-p-dioxins (PCDDs) and polychlorinated dibenzofurans (PCDFs) were detected, although these levels never exceeded 20 pg/g (wet wt). The major contributor to total toxic equivalent quantities (TEQs) were non– ortho-PCBs. Organochlorine levels found in this study may contribute to the entire suite of stressors that are negatively affecting the peregrine population. Financial support for this research was provided by the project 186/RN-38 Consejería de Agricultura y Medio Ambiente de la Junta de Comunidades de Castilla-La Mancha. Sociedad Española de Ornitología Birdlife helped to finance this research. Peer reviewed